Case Series: Anaesthetic Management Of Paediatric Patients Of Age Group 1 Month To 5 Years With Hydrocephalus Posted For Ventriculoperitoneal Shunt Surgery - Dixit R, Haizal; Shaikh, Arshiya; Prudhvi, Bandaru (Journal of Neonatal Surgery, 2025)
Introduction: Hydrocephalus is the abnormal enlargement of the cerebral ventricles caused by a disruption in the normal flow of cerebrospinal fluid (CSF). In children over the age of two, signs of intracranial pressure increase are more likely to be seen, often accompanied by progressive enlargement of the head. The surgical placement of a shunt is the primary treatment for hydrocephalus in cases with worsening neurological symptoms or significant increase in head size. Aims and Objectives: The perioperative anaesthetic management of a child with severe hydrocephalus is challenging due to the increased head size and possible associated congenital heart defects and neural tube abnormalities. Materials and Methods: This case report discusses a child with severe hydrocephalus scheduled for emergency ventriculo-peritoneal (VP) shunt placement who presented with a difficult airway. A towel was placed beneath the shoulders to facilitate intubation, and the child was positioned properly with a difficult airway cart on standby. Anaesthesia was induced with sevoflurane inhalation, and after reaching adequate depth, the child was intubated on the first attempt using a Macintosh blade size 1. A 3.5 mm ID uncuffed endotracheal tube was inserted and secured at 9 cm after confirming equal bilateral breath sounds. During surgery, the child was maintained on a mixture of oxygen, nitrous oxide, and sevoflurane. Conclusion: Managing a child with severe hydrocephalus is challenging due to potential airway difficulties, positioning issues, and associated congenital anomalies. Ensuring proper positioning and preparing for a difficult airway are critical for safe anaesthesia management